(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The most prevalent rising health risk for women of reproductive age is polycystic ovarian syndrome, a heterogeneous endocrine condition. The polycystic ovarian syndrome (PCOS) is a prevalent endocrinopathy that is multifactorial and polygenic and is characterized by several tiny ovarian cysts, oligo-ovulation or anovulation, and indicators of hyperandrogenism, differ from person to person throughout time. Here is a case report of a 15-year-old girl who presented with hirsutism, irregular menstruation and constipation, her USG report showed bilateral PCO pattern. Based on the clinical features, treatment principles adopted are Aam paachana, use of Arthava janana Dravya, Vata anulomana and Granthi nashak chikitsa. Initially, after 2 months of treatment menstruation became normal and marked reduction in the symptoms was found. Moreover, the hormonal level became normal after 6 months of treatment. This case study is an example that PCOS can be effectively managed by adhering to Ayurvedic principles.